Chemical and biological investigation of the Agaricus silvaticus Schaeff ex. Secr - Munkhgerel, L; Erdenechimeg, N; Dumaa, M; Zhang, G; Odonmajig, P; Regdel, D (Mongolian Journal of Chemistry, 2014)
Extract of Agaricus silvaticus Schaeff ex. Secr fungus have been known to have biological activities, including antibacterial, antiviral, anticancer, antioxidant, anticomplementary and immunostimulating effects. In this study we first time identified that Agaricus silvaticus Schaeff ex. Secr has interferon like activity. We first time isolated the four known compounds such as, mannitol (1), urea (2), ergosterol (3) and ergosterol peroxide (4) from 95% ethanol extracts of Agaricus silvaticus Schaeff ex. Secr in Mongolia. Their structures were elucidated on the basis of extensive analysis of spectral data and by comparison with authentic samples. DOI: http://dx.doi.org/10.5564/mjc.v12i0.180 Mongolian Journal of Chemistry Vol.12 2011: 92-97